IDENTIFIKASI JAMUR YANG TERBAWA BIJI EMPAT KLON KAKAO (Theobroma cacao L.) PADA PENANGANAN ASALAN DAN PENANGANAN TERKENDALI - Nurdin, Muhammad; Evizal, Rusdi; Akin, Hasriadi Mat; Safitri, Annisa (JURNAL AGROTROPIKA, 2025)
Identification is an important activity in the management of plant diseases because by knowing the identity of the fungus found in cocoa beans, a strategy can be determined as a first step before controlling the fungus to prevent the spread of the fungus. This research aims to determine the fungi associated with the MCC 01, MCC 02, Sulawesi 1, and THR clones on uncontrol handling and controlled handling cocoa beans and to determine whether uncontrol handling and controlled handling reduce inoculum sources to suppress fungi growth and development. This research was conducted at the Laboratory of Plant Diseases, Faculty of Agriculture, University of Lampung from January 2023 to March 2023. This research was carried out by testing the agar method (agar plate), the media used was potato sucrose agar (PSA). There were four samples of cocoa bean clones, namely MCC 01, MCC 02, Sulawesi 1, and THR from Kuta Dalom Village, Pesawaran Regency, which were grown on 128 plates of PSA media (64 plates using 2% NaOCl and 64 plates without NaOCl) for each clone. Cocoa beans contained 32 cups each uncontrol handling and controlled handling. So there are 128 cups of PSA media. Isolates that have been obtained are then identified 7 days after isolation. Observations in this study were carried out macroscopically and microscopically. Macroscopic observations were carried out to differentiate growing fungi based on the color, shape and size of the colonies. Meanwhile, microscopic observations were made to differentiate growing fungus based on the structure of the fungi body. The results showed that from the uncontrol handling and the controlled handling, three fungi were found, namely Aspergillus flavus, Aspergillus niger, and Rhizoctonia sp. The fungi Aspergillus flavus and Aspergillus niger show that controlled handling can reduce the source of inoculum compared to uncontrol handling. In contrast to the fungi Aspergillus flavus and Aspergillus niger, the fungi Rhizoctonia sp. shows that controlled handling cannot reduce the source of inoculum. Key words:  Aspergillus, bean, cocoa, Rhizoctonia, handling